A blood biomarker and clinical correlation cohort study protocol to diagnose sports-related concussion and monitor recovery in elite rugby. Issue 1 (27th November 2020) - Kearns, Jamie; Ross, Aisling M; Walsh, Darragh R; Cahalane, Rachel M; Hinchion, Rita; Ryan, Maria C; Conway, Elaine; Comyns, Tom M; Kenny, Ian C; O'Connor, Eibhlís M; McGourty, Kieran D; Mulvihill, John Joseph Eugene
Abstract : Introduction: In professional rugby, sports-related concussion (SRC) remains the most frequent time loss injury. Therefore, accurately diagnosing SRC and monitoring player recovery, through a multi-modal assessment process, is critical to SRC management. In this protocol study, we aim to assess SRC over multiple time points post-injury to determine the value of multi-modal assessments to monitor player recovery. This is of significance to minimise premature return-to-play and, ultimately, to reduce the long-term effects associated with SRC. The study will also establish the logistics of implementing such a study in a professional setting to monitor a player's SRC recovery. Methods and analysis: All players from the participating professional rugby club within the Irish Rugby Football Union are invited to participate in the current study. Player assessment includes head injury assessment (HIA), neuropsychometric assessment (ImPACT), targeted biomarker analysis and untargeted biomarker analysis. Baseline HIA, ImPACT, and blood draws are performed prior to the start of playing season. During the baseline tests, player's complete consent forms and an SRC history questionnaire. Subsequently, any participant that enters the HIA process over the playing season due to a suspected SRC will be clinically assessed (HIA and ImPACT) and their blood will be drawn within 3 days of injury, 6 days post-injury, and 13 days post-injury. Ethics and dissemination: Ethical approval was attained from the Science and Engineering Research Ethics Committee, University of Limerick (Approval Code: 2018_06_11_S&E). On completion of the study, further manuscripts will be published to present the results of the tests and their ability to measure player recovery from SRC. Trial registration number: NCT04485494.